Environmental Taxes and Food Exports: Assessing Trade and Sustainability Dynamics in OECD Countries - Gafsi, Nesrine; Bakari, Sayef (International Journal of Energy Economics and Policy, 2026)
This study investigates the impact of environmental taxes on food exports in OECD countries from 1994 to 2022, utilizing advanced econometric techniques, including panel cointegration analysis and Panel Vector Error Correction Models (Panel VECMs). While environmental taxation aims to mitigate ecological degradation, its trade implications remain debated. The results reveal a positive long-term relationship between environmental taxes and food exports, suggesting that taxation policies incentivize sustainable innovation and enhance export competitiveness. However, short-term effects indicate a temporary decline in food exports following tax increases. The study also identifies a bidirectional causal relationship between environmental taxation and food exports, highlighting the role of regulatory adaptation and market adjustments. These findings provide critical insights for policymakers seeking to balance trade competitiveness and environmental sustainability through well-designed taxation frameworks and international policy coordination.